The Impact of Employee Motivation on Productivity - Bestadrian Prawiro Theng; Robin (Universitas Muhammadiyah Palu, 2023)
Productivity refers to the capability of employee in making significant achievements which are higher than the company expectations. It means that the outcome of the work is better than what the company expect them to do. Employee productivity can be realized if the human resource is able to be responsible in accomplishing the task or job. One of the key factors which influence productivity is employee motivation. The problem at UD Segren Binjai are the lacking of productivity in terms of coming to work late and not accomplishing the task on time. The research designs used in this study are descriptive study and correlative study. In this research, the writer used questionnaire to collect the data. The sample used in this study is the employees at UD Segren Binjai which are 33 employees. The result got from this research is the employee motivation has impact on productivity at UD Segren Binjai which can be seen from the hypothesis test (zcount > ztable (4.28 > 1.96)) which means that the Ho is rejected and the Ha is accepted. From the correlation test done, it shows the result is 0.771 which means that employee motivation has strong and positive impact on productivity.